IMPLEMENTATION OF FLEXIBLE WORKING ARRANGEMENT AT THE DEPUTY FOR INSTITUTIONAL AND COMMUNITY RELATIONS OF THE MINISTRY OF STATE SECRETARIAT - Triyani, Septina; Sutrino, Edy; Widjayanti, Arifiani (DIA: Jurnal Administrasi Publik, 2025)
The advancement of ICT has driven changes in work patterns known as flexible working arrangements (FWA). FWA not only has a positive impact on employees and their organizations, but also a negative impact in its implementation. The study aims to analyze the inhibiting factors for the suboptimal implementation of FWA at the Deputy for Institutional and Community Relations at the Ministry of State Secretariat and to provide strategies to optimize FWA. FWA was initiated to improve employee work flexibility, employee performance and job satisfaction, and work-life balance. The study used a descriptive qualitative method with data collection techniques through in-depth interviews and documentation studies. Based on Merilee S. Grindle's policy implementation approach, the analysis focused on two main variables: policy content and implementation context. The results of the study indicate that the implementation of FWA is supported by the Minister of State Secretary, and organizational unit leaders, as well as employees who have high commitment. However, the main obstacles found were: the type of benefit factor, the degree of change factor, the technological resource factor, and the program implementer factor. Strategies to optimize FWA include: submitting a proposal to Deputy AA regarding the need for a ministerial decree related to the implementation of FWA in order to provide strong legal certainty, consistency in implementation, and legal certainty in its application in the Ministry of State Secretariat in general; aligning business process documents, service standards, and SOPs in order to provide clear guidance to employees in the implementation of FWA and the implementation of tasks that are adjusted to current changes; and increasing the stability and integration of office applications supporting FWA.